Politeness in the Comment Section of the YouTube Channel Entertainment News - Syahputra, Bambang Panca; Anggreani, Fyzza; Amri, Yusni Khairul (Universitas Pahlawan Tuanku Tambusai, 2024)
YouTube is a popular platform utilized by a diverse range of people for various purposes, such as documentary videos, the latest news, tutorials, and more. As a result, a wide variety of speech styles can be found on the platform, reflecting different levels of politeness. This analysis was conducted to explore politeness in language within the comments section of a specific video. The source for this research is the video titled